PENGARUH PENDIDIKAN TERHADAP STRATA SOSIAL MASYARAKAT DI ZAMAN KLASIK DALAM PANDANGAN IMAM AL- GHAZALI - Aritonang, Dikot (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2023)
This research reviews the influence of education on the social strata (economicproblems) of humans in the classical era as viewed from the thoughts of ImamAl-Ghazali. The problem in this research is Imam Al-Ghazali's view of theconcept of education. Al-Ghazali believes that an educator is a human figurewho totally concentrates on the field of education. He cannot do other activities.But on the other hand, he may receive proportional material rewards to meet hisliving needs. The research method used is a qualitative method in the form ofliterature research. The research results obtained are Al-Ghazali's educationalthoughts which can be seen from several things, namely: First, Al-Ghazali'seducational thought is religious-ethical and places science in a very honorableposition. Education is a means of getting closer to Allah SWT which can leadhumans to achieve happiness in this world and the hereafter. Second, Al-Ghazali's educational goals include three aspects, namely the cognitive aspect,which includes the development of reasoning, such as intelligence, intelligenceand thinking power; affective aspect, which includes heart formation, such asthe development of feelings, heart and spirituality; and psychomotor aspects;namely physical development, such as body health and skills.